THE IMPACT OF TRANSFER PRICING, CAPITAL INTENSITY, AND POLITICAL CONNECTION ON TAX AGGRESSIVENESS (SURVEY OF MANUFACTURING COMPANIES IN THE PHARMACEUTICAL SUB SECTOR LISTED ON IDX FOR 2017-2021) - NICOLAS K SIHOTANG; LENITA WATY (CV KULTURA DIGITAL MEDIA, 2022)
This study aims to partially or simultaneously examine the impact of transfer pricing, capital intensity, and political connections on tax aggressiveness. This study uses pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for 2017-2021. The sample collection technique was carried out using a purposive sampling method, which in the end, obtained a total of 35 samples. The multiple regression method was used for data analysis. The results showed that transfer pricing, capital intensity, and political connection had no significant effect on tax aggressiveness partially or simultaneously.